Efficient coupling of dual beam combined laser into micro water jet for deep processing - Ji Wang; Chunguang Chen; Guolong Wang; Kaijie Cheng; Wenwu Zhang (Scientific Reports)
Abstract In order to improve the power and energy of water-jet-guided laser, this paper introduces a double beam water-jet-guided laser (DWJL) technology. Based spatially polarized light combination and temporal phase modulation, two lasers are effectively coupled into a water jet with diameter of 100 μm. The maximum output peak power reaches 100 kW and the maximum pulse energy is 4.63 mJ with an operation frequency range from 1 to 20 kHz. The coupling efficiency is as high as 90.4%. Its efficient energy utilization offers new solutions for precision cutting and processing of thick materials. Ultimately, the machining capability of high-power/high-energy DWJL was demonstrated by cutting through 7075 aluminum alloys of varying thicknesses. The cutting depth reaches 10.61 mm, corresponding to a depth-to-width ratio of the cutting gap exceeds 90:1, and the taper is only approximately 0.23°. There is no heat-affected ablation zone on the processed surface. For deep micro holes processing, a minimum radius is 248.54 μm with a depth-to-diameter ratio of 21:1. As the ongoing development of DWJL technology, this innovation is anticipated to find broader applications in aerospace, automotive manufacturing, and high-end equipment manufacturing in the future.